The economics of the environment and natural resources - Grafton, Quentin R. 1962- (Blackwell Pub. Ltd, 2004)
This text covers the essential topics students need to understand environmental and resource problems and their possible solutions. Its lecture format provides an in-depth exploration of discrete topics, ideal for upper-level undergraduate, graduate or doctoral study.